2020
DOI: 10.11594/jtls.10.01.01
|View full text |Cite
|
Sign up to set email alerts
|

Potentials of Hydrocarbon Utilization by Wood-Digesting Bacteria isolated from the Lagos Lagoon, Nigeria.

Abstract: There is a continuous search for environmental-friendly methods to address oilpolluted environments, hence this study aimed to establish the potential of using tropical estuarine bacterial strains for degradation of crude oil in polluted environment. Microbial degradation of hydrocarbons has been considered a promising, natural, less toxic and cost-effective technology. Lignocellulose-utilizing bacterial strains (Bacillus megaterium strain NOB, Streptomyces pseudogriseolus strain EOB and Paenibacillus sp. stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Ragi tapai is a dry starter culture made from rice flour, spices, and water or sugarcane juice/extract [9,10]. Various amylolytic and fermentative microbes have been isolated from various brands of ragi tapai acquired from various places and markets, such as Amylomyces rouxii, Rhizopus oryzae, Endomycopsis burtonii, Mucor sp., Candida utilis, Saccharomycopsis fibuligera, Saccharomyces cerevisiae and some lactic acid bacteria Pediococcus pentosaceus, Lactobacillus plantarum, and L. fermentum [10][11][12]. Studies from the Philippines, Malaysia, Thailand, and Vietnam found similar microbial species in the inoculum of tapai [10].…”
Section: Introductionmentioning
confidence: 95%
“…Ragi tapai is a dry starter culture made from rice flour, spices, and water or sugarcane juice/extract [9,10]. Various amylolytic and fermentative microbes have been isolated from various brands of ragi tapai acquired from various places and markets, such as Amylomyces rouxii, Rhizopus oryzae, Endomycopsis burtonii, Mucor sp., Candida utilis, Saccharomycopsis fibuligera, Saccharomyces cerevisiae and some lactic acid bacteria Pediococcus pentosaceus, Lactobacillus plantarum, and L. fermentum [10][11][12]. Studies from the Philippines, Malaysia, Thailand, and Vietnam found similar microbial species in the inoculum of tapai [10].…”
Section: Introductionmentioning
confidence: 95%